A survey on the initial management of spontaneous pneumothorax - How, Soon Hin; T, Ismail; M F, Anshar; C W A, Hashim; W H W, Mohamad; D, Katiman (Malaysian Medical Associations, 2010)
condition but continues to be a frequent management problem among doctors. Despite the availability of guidelines on management of SP, studies have shown that the compliance with the guidelines is low. The various treatment options available in treating this condition further confuse doctors on the right approach in managing SP. The objective of this study is to investigate the awareness of the availability of these existing guidelines and to investigate how the doctors involved in the initial management of SP would manage this condition. A self completed questionnaire which included three case scenarios were distributed among doctors in two teaching university hospitals and two large Ministry of Health hospitals. This study showed that there is a lack of awareness of the existing guidelines even among the senior doctors and there is a variation in the initial management of SP. Therefore a locally produced guideline may be beneficial to standardise and improve the management of SP.